2019
DOI: 10.29086/jisfteh.7.e8
|View full text |Cite
|
Sign up to set email alerts
|

2019: The Year of Teledentistry in France?

Abstract: In France, access to a dentist for elderly people, disabled people or inmates is limited. A person's access to a dentist decreases by 25% when joining a nursing home. A national report mentioned that 85% of residents in nursing homes didn't have access to a dentist in the past year and 42% in the last 5 years. There are fewer data on disabled people, but 48% of people with disabilities have, at least, one important issue related to oral health. Two examples of teledentistry, the e-DENT project from University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“… 11 Unfortunately, the impossibility for dentists to be provided with remuneration from the French national health insurance plan may have made it difficult to implement and develop TD on a national basis to date. [ 12 ] From this study, 39.2% (n = 1982) stated that they already practice TD which does not match the national situation, however, the misunderstanding of the terminology employed may be a reason for it. Dentists from this study did not know that TD is an officially and legally regulated medical activity and not merely an act of giving advice over the phone.…”
Section: Discussionmentioning
confidence: 78%
“… 11 Unfortunately, the impossibility for dentists to be provided with remuneration from the French national health insurance plan may have made it difficult to implement and develop TD on a national basis to date. [ 12 ] From this study, 39.2% (n = 1982) stated that they already practice TD which does not match the national situation, however, the misunderstanding of the terminology employed may be a reason for it. Dentists from this study did not know that TD is an officially and legally regulated medical activity and not merely an act of giving advice over the phone.…”
Section: Discussionmentioning
confidence: 78%
“…Also, dentists reported that teledentistry is a useful tool to connect directly with patients/ caregivers, and it is very useful making a first evaluation. 3,4,9 In Australia, the teledentistry approach for diagnosis and consultations of the underserved, high-risk population with major oral health needs was explored by comparing face-to-face examinations and remote examinations using an intraoral camera. A total of 50 individuals participated and it is suggested that teledentistry is a feasible and reliable alternative to traditional methods, in particular, for oral health screening.…”
Section: Disaster Medicine and Public Health Preparednessmentioning
confidence: 99%
“…Regardless of the teledentistry service formats, a high satisfaction rate in the present study echoes the results of the previous research. 4,9,23 Telemedicine can be applied in a synchronous (real time) or asynchronous (store-and-forward mode) manner. 8,24 In a systematic review about the telemedicine applications among rural individuals with disabilities, it was reported that generally videoconferencing was used for synchronized intervention, in which local care providers, patients, caregivers, and the remote care team could interact in real time.…”
Section: Disaster Medicine and Public Health Preparednessmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical validation of this camera for a remote diagnosis allows us to consider teledentistry activity. 29 To do so, a number of points need to be addressed:…”
Section: Development Of Teledentistry Using Fluorescencementioning
confidence: 99%